Dual mechanisms of GABAA response inhibition by beta-lactam antibiotics in the pyramidal neurones of the rat cerebral cortex. - Fujimoto, M. (1995)
1. The effects of beta-lactam antibiotics on the gamma-aminobutyric acid (GABA)-induced Cl- current were investigated in pyramidal neurones freshly dissociated from the rat frontal cortex by the use of a nystatin-perforated patch recording mode under voltage-clamp conditions. 2. The GABA-induced inward current increased in a concentration-dependent manner with an EC50 of 6.7 x 10(-6) M at a holding potential of -40 mV. The GABA response was accompanied by an increase in the membrane conductance and reversed at near the Cl- equilibrium potential. 3. All beta-lactams (penicillin, imipenem, aztreonam and cefotiam) inhibited the 10(-5) M GABA-induced response in a concentration-dependent manner with an IC50 and Hill coefficient of 1.3 x 10(-3) M and 0.64 for penicillin, 9.6 x 10(-4) M and 0.83 for imipenem, 2.5 x 10(-3) M and 9.99 for aztreonam, and 2.9 x 10(-4) M and 1.03 for cefotiam. 4. Imipenem inhibited the GABA-response competitively while penicillin inhibited the same response in a noncompetitive fashion. 5. The inhibitory action of imipenem showed no voltage-dependency, whereas the effect of penicillin was voltage-dependent. 6. It is thus proposed that some classes of beta-lactams, including imipenem may have a mechanism that is different from penicillin and competitively affects the GABAA receptor.